Advanced treatment in basal cell carcinoma of skin - Gupta, Pankaj Kumar; Wan, Xuefeng; Kanduri, Hari Krishna; Goud, Kurelli Sai Charan; Abliz, Paride; Sulaiman, Akebaier (International Journal of Research in Dermatology, 2019)
In the past ten years, the occurrence of basal cell carcinoma (BCC) has amplified manifold. There are many treatment procedures to cure BCC, which includes micrographic surgery by means of surgical margins of 3-5mm based on size of tumor, intrusion and location. The normally used method for treatment of basal cell carcinoma is excision by surgery. The most commonly used advanced method of excision in the treatment of bcc is Mohs’ micrographic surgery (MMS). There is no proper guideline, which mentions surgery as the treatment of choice as there are no controlled randomized studies matching surgery with nonsurgical treatment options in BCC. Excision is a competent and meticulous technique as there is a low recurrence of tumor following the histological examination of tumor margins.